"Patent Property": The Fulton Lawyers and the Franchising of Progress. Issue 1 (2nd December 2017) - Milford, Timothy
ABSTRACT: Cadwallader D. Colden and Thomas Addis Emmet could not help but practice intellectual property law: Robert Fulton was their client. Yet their engagement with the subject went far beyond what professional expediency demanded. Their transatlantic backgrounds and careers encouraged their affinity for liberal political economy and for entrepreneurial adventure. On the frontier, in the shadowy zones between early-nineteenth-century empires and land speculations, the line between enterprise and piratical intrigue was easily leapt, and Colden and Emmet were involved in the era's cross-border confusions. More typically, their work anticipated a world where private business and public improvement were managed in tandem, by interested franchisees, and underwritten by more sophisticated financial arrangements. The defense of Fulton's patent privileges was an unabashed apology for banks, corporations, and wealth. These lawyers celebrated canals and steamboats and argued that such tangible achievements were impossible without a flexible understanding of property. Their practice was bound up in the franchise model of development and reconciled government patronage with what was then, and is still, a controversial and liberal vision of progress.